Steamboat PROSPECTOR leaving Dawson, Yukon Territory, 1902. - University of Washington Libraries. Special Collections Division
PH Coll 246.200 [Meed journal: ""Prospector" leaving Dawson. (view toward stern)"] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number